Bevacizumab and platinum-based combinations for recurrent ovarian cancer: a randomised, open-label, phase 3 trial. Issue 5 (May 2020) - Pfisterer, Jacobus; Shannon, Catherine M; Baumann, Klaus; Rau, Joern; Harter, Philipp; Joly, Florence; Sehouli, Jalid; Canzler, Ulrich; Schmalfeldt, Barbara; Dean, Andrew P; Hein, Alexander; Zeimet, Alain G; et al.
Summary: Background: State-of-the art therapy for recurrent ovarian cancer suitable for platinum-based re-treatment includes bevacizumab-containing combinations (eg, bevacizumab combined with carboplatin–paclitaxel or carboplatin–gemcitabine) or the most active non-bevacizumab regimen: carboplatin–pegylated liposomal doxorubicin. The aim of this head-to-head trial was to compare a standard bevacizumab-containing regimen versus carboplatin–pegylated liposomal doxorubicin combined with bevacizumab. Methods: This multicentre, open-label, randomised, phase 3 trial, was done in 159 academic centres in Germany, France, Australia, Austria, and the UK. Eligible patients (aged ≥18 years) had histologically confirmed epithelial ovarian, primary peritoneal, or fallopian tube carcinoma with first disease recurrence more than 6 months after first-line platinum-based chemotherapy, and an Eastern Cooperative Oncology Group performance status of 0–2. Patients were stratified by platinum-free interval, residual tumour, previous antiangiogenic therapy, and study group language, and were centrally randomly assigned 1:1 using randomly permuted blocks of size two, four, or six to receive six intravenous cycles of bevacizumab (15 mg/kg, day 1) plus carboplatin (area under the concentration curve [AUC] 4, day 1) plus gemcitabine (1000 mg/m 2, days 1 and 8) every 3 weeks or six cycles of bevacizumab (10 mg/kg, days 1 and 15) plus carboplatin (AUC 5, day 1) plus pegylated liposomal doxorubicin (30 mg/m 2, day 1) every 4 weeks, both followed by maintenance bevacizumab (15 mg/kg every 3 weeks in both groups) until disease progression or unacceptable toxicity. There was no masking in this open-label trial. The primary endpoint was investigator-assessed progression-free survival according to Response Evaluation Criteria in Solid Tumors version 1.1. Efficacy data were analysed in the intention-to-treat population. Safety was analysed in all patients who received at least one dose of study drug. This completed study is registered with ClinicalTrials.gov, NCT01837251 . Findings: Between Aug 1, 2013, and July 31, 2015, 682 eligible patients were enrolled, of whom 345 were randomly assigned to receive carboplatin–pegylated liposomal doxorubicin–bevacizumab (experimental group) and 337 were randomly assigned to receive carboplatin–gemcitabine–bevacizumab (standard group). Median follow-up for progression-free survival at data cutoff (July 10, 2018) was 12·4 months (IQR 8·3–21·7) in the experimental group and 11·3 months (8·0–18·4) in the standard group. Median progression-free survival was 13·3 months (95% CI 11·7–14·2) in the experimental group versus 11·6 months (11·0–12·7) in the standard group (hazard ratio 0·81, 95% CI 0·68–0·96; p=0·012). The most common grade 3 or 4 adverse events were hypertension (88 [27%] of 332 patients in the experimental group vs 67 [20%] of 329 patients in the standard group) and neutropenia (40 [12%] vs 73 [22%]). Serious adverse events occurred in 33 (10%) of 332 patients in the experimental group and 28 (9%) of 329 in the standard group. Treatment-related deaths occurred in one patient in the experimental group (<1%; large intestine perforation) and two patients in the standard group (1%; one case each of osmotic demyelination syndrome and intracranial haemorrhage). Interpretation: Carboplatin–pegylated liposomal doxorubicin–bevacizumab is a new standard treatment option for platinum-eligible recurrent ovarian cancer. Funding: F Hoffmann-La Roche.